2018
DOI: 10.1021/acs.jmedchem.8b00357
|View full text |Cite
|
Sign up to set email alerts
|

Tight-Binding Inhibition of Human Monoamine Oxidase B by Chromone Analogs: A Kinetic, Crystallographic, and Biological Analysis

Abstract: Monoamine oxidase B (MAO-B) is a validated drug target for Parkinson's disease. Chromone derivatives were identified as novel potent and reversible MAO-B inhibitors, and herewith we report on a crystallographic and biochemical analysis to investigate their inhibition mechanism. The crystal structures of human MAO-B in complex with three chromone analogs bearing different substituents on the exocyclic aromatic ring (determined at 1.6-1.8 Å resolution) showed that they all bind in the active site cavity of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…To maintain pharmacological efficacy, they are aimed to show a high affinity towards the MAOs and/or tight binding behavior. 9 The design of such reversible and selective inhibitors of MAO A and B became a strongly researched area to identify suitable drug candidates for the treatment of neurological diseases, particularly of PD.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain pharmacological efficacy, they are aimed to show a high affinity towards the MAOs and/or tight binding behavior. 9 The design of such reversible and selective inhibitors of MAO A and B became a strongly researched area to identify suitable drug candidates for the treatment of neurological diseases, particularly of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Reis et al studied the MAO‐B inhibition mechanism by means of crystallographic and biochemical analysis (Figure ). The crystal structures of hMAO‐B in complex with three chromone analogs N ‐(3′,4′‐dimethylphenyl)‐4‐oxo‐4 H ‐chromene‐3‐carboxamide ( 259 ), N ‐(3′‐chlorophenyl)‐4‐oxo‐4 H ‐chromene‐3‐carboxamide ( 260 ), and N ‐(3′‐fluorophenyl)‐4‐oxo‐4 H ‐chromene‐3‐carboxamide ( 261 ) bearing different substituents on the exocyclic aromatic ring (determined at 1.6‐1.8 Å resolution) showed that they all bind in the active site cavity of the protein with the chromone moiety located in front of the FAD cofactor.…”
Section: Molecular Modeling Studies On Mao‐b and Its Inhibitorsmentioning
confidence: 99%
“…Structure and MAO‐B inhibitory profile of chromone analogs ( 259 ‐ 261 ) hMAO, human monoamine oxidase…”
Section: Molecular Modeling Studies On Mao‐b and Its Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromone, especially C3‐substituted chromone, is recognized as a privileged template for the design of novel compounds with potential pharmacological interest in the field of neurodegenerative, inflammatory, and infectious diseases as well as diabetes and cancer . For example, 3‐sulfonylchromone derivatives were developed as α‐glucosidase inhibitor due to the noteworthy antioxidant activity .…”
Section: Introductionmentioning
confidence: 99%